ANALISIS MODEL BISNIS BERBASIS EKOSISTEM APLIKASI GO-JEK DALAM MENINGKATKAN KEPUASAN DAN LOYALITAS PELANGGAN - Romadhoni, Muhammad Adey; Maika, M. Ruslianor (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2021)
This study aims to find out how important the service ecosystem in the Go-Jek application. While the methodology used in this research is qualitative with a phenomenological approach. Data collection process was hindered by the presence of Covid-19 which had plagued Indonesia since March 2020, which affected the data collection techniques that researchers used, and the types of data researchers obtained. Respondents was 40 active students of the Muhammadiyah University of Sidoarjo. The research conducted by the author regarding the users experience, as many as 16 informants said that they had experienced poor service from Gojek driver partners. Meanwhile, 24 informants said they had never experienced poor service, meaning that the majority of the informants received good service from Gojek driver partners. Most of the respondents feel very helpful with every service in the Go-Jek application, so that the level of satisfaction with the services from Go-Jek is very high.